The Effect of Gamification on Learning Motivation and Positive Perceptions of Economics in the Tenth Grade of High School - Mustaman Mustaman; Elpisah Elpisah; Saripuddin Saripuddin; Suarlin Suarlin (International Forum of Researchers and Lecturers, 2026)
This study aims to (1) analyze the effect of gamification on students’ learning motivation and (2) analyze the effect of gamification on students’ positive perceptions in economics learning among Grade X students at SMAN 1 Pangkep. This research employed a quantitative approach with an ex post facto design and involved 198 students selected through proportional random sampling. A Likert-scale questionnaire was used as the main research instrument to measure the variables of gamification, learning motivation, and positive perception. Data analysis was conducted using simple linear regression to identify relationship patterns and determine the magnitude of influence of the independent variable on both dependent variables. The results of the study indicate that gamification has a positive and significant effect on student learning motivation. In addition, gamification also has a positive and significant effect on students' positive perceptions of economics learning. These findings indicate that the application of gamification elements in learning can encourage student engagement, increase learning motivation, and create a more interesting, enjoyable, and meaningful learning experience..